Improved Ratio-type Exponential Estimator for Estimating Population Mean in Ranked Set Sampling - Nirupama Sahoo; Sananda Kumar Jhankar (Journal of the Indian Society of Agricultural Statistics, 2025)
In this paper we propose a ratio-type exponential estimator for estimating population mean of the study variable under Ranked set sampling when auxiliary information is known. The bias and Mean square error of the proposed estimator has been derived up to the first degree of approximation. A simulation study has been carried out to judge the performance of the newly proposed estimator along with existing estimators. It is obtained that the proposed estimator is more efficient as compared to the competing estimators.